1995
DOI: 10.1002/ajmg.1320580404
|View full text |Cite
|
Sign up to set email alerts
|

Transient leukemia with trisomy 21: Description of a case and review of the literature

Abstract: Transient myeloproliferative disease (TMD) is often associated with a trisomy 21 cell line, but it is not always associated with clinical signs of Down syndrome. We report on a phenotypically normal newborn boy who presented with a high white blood cell count, undifferentiated blasts, and cutaneous leukemic infiltrates and compare this patient with the literature on TMD and trisomy 21. Chromosome analysis of bone marrow, and subsequently of skin fibroblasts, documented constitutional mosaicism for trisomy 21. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 18 publications
(28 reference statements)
0
15
1
1
Order By: Relevance
“…Unlike in patients with Down’s syndrome, recurrence requiring therapeutic intervention has not yet been reported in patients with TMD and a normal constitutional karyotype, although it has been seen in a case of constitutional trisomy 21 mosaicism without phenotypic features of Down’s syndrome 15. There was no evidence of mosaicism in the tissues examined in our cases.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Unlike in patients with Down’s syndrome, recurrence requiring therapeutic intervention has not yet been reported in patients with TMD and a normal constitutional karyotype, although it has been seen in a case of constitutional trisomy 21 mosaicism without phenotypic features of Down’s syndrome 15. There was no evidence of mosaicism in the tissues examined in our cases.…”
Section: Discussioncontrasting
confidence: 54%
“…6 8-14 These all achieved complete haematological and cytogenetic remission, without evidence of recurrence or evolution to acute leukaemia at periods of follow up varying from six months to six years. This contrasts with the prevalence of acute myeloid leukaemia following TMD in Down’s syndrome patients, variously reported as 25%15 and 33% 4…”
Section: Discussionmentioning
confidence: 68%
“…In rare cases, TMD is accompanied by vesiculopustular eruption. [3][4][5][6][7][8][9][10][11][12][13] We report an infant with DS showing TMD and skin lesions, in whom genetic analyses detected a somatic mutation of GATA-1 197G[T(Glu295Stop).…”
mentioning
confidence: 99%
“…It has also been reported that DS children have a 400‐fold higher risk of developing a unique subtype of an acute megakaryoblastic leukemia [French American British (FAB) classification: acute non‐lymphoblastic leukemia‐M7 (ANLL‐M7)], compared with the general population 7. This type of leukemia is considered to be similar to TLD, in that both diseases involve a megakaryoblastic displasia of bone marrow 8–11…”
mentioning
confidence: 99%
“…The fact that Trisomy 21 is the most frequent chromosomal aberration in tumor cells of ANLL patients with a normal karyotype has led to an assumption that excess of chromosome 21 is a possible cause for the susceptibility of DS subjects to leukemia 4, 5, 11. This hypothesis was later supported by the fact that several oncogenes were identified on the long arm of chromosome 21 5, 8, 12.…”
mentioning
confidence: 99%